RIGIDIZATION OF MENTAL IMAGES AS DYSFUNCTION OF PICTURES RECOGNITION - Hovhannisyan, H. R.; Manukyan , A. A. (Modern Psychology, 2019)
This article illustrates the unique effect of human visual perception: during the recognition of images specially distorted by a computer program, the subject spontaneously “creates and strengthens” the imaginary contours of the presented stimulus material. Piloting experimentally, we found that sometimes during the observation of the process of gradual clarification of completely distorted pictures, 50 the recognition by the subjects is complicated, because the signs of a previously fancied imaginary contour are enhanced. The observer seemed to be “under the influence of an fancy imaginative scenario”, as a result of which the “contour attribution” retained its increasing power, thereby making the mental image rigid. As a result, the recognition function of the gradually becoming clearer image was temporarily blocked (disordered).